The Asymmetric Effects of Macroeconomic Performance on Happiness: Evidence for the EU - Edsel L. Beja (Intereconomics, 2017)
An analysis of data from the Eurobarometer finds evidence of the asymmetric effects of macroeconomic performance on happiness. The evidence reveals that the negative effect of an economic recession on happiness can be at least twice the positive effect of economic growth. In short, a single year of recession can undo the happiness gains from years of economic growth. Moreover, while this evidence focuses on a short-run asymmetry, it nonetheless supports the Easterlin paradox of a nil relationship between macroeconomic performance and happiness. The evidence indicates that stable rather than rapid economic growth is a more sensible target for policymakers, because macroeconomic stability can lead to conditions that allow the pursuit of happiness and thus secure greater well-being.
Keywords: 330